El impacto cultural del cine de los países socialistas en Argentina (1954-1970) - Galván, Maria Valeria (2017)
The aim of this paper is to study a specific aspect of the Soviet foreign propaganda policy in Latin America: its cultural influence through the export of films. Renewed after Stalin´s death, Communist cultural propaganda concentrated on gaining the favor of foreign public. Particularly in Argentina, several propaganda techniques were implemented. Although the export of films was just one of them, it soon became very successful thanks to the collaboration of a local cultural mediator, the film distribution company Artkino Pictures, as well as its owner and founder, Argentino Vainikoff. His expertise in the field actually gained him a new business deal with Czechoslovak filmography, which somewhat contested USSR imaginary. In all, here –with the aid of oral history as well as contemporary press analysis– we argue that Artkino´s role in the import of an idealized imaginary of Communism was crucial and had a particularly strong impact on middle-class citizens of the cultural and artistic regional center that Buenos Aires was in the fifties and sixties, and from where all Latin America, as the Soviets soon acknowledged, could be reached.